The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/19475705.2017.1417332
|View full text |Cite
|
Sign up to set email alerts
|

Climatic, geomorphic and anthropogenic drivers of the 2014 extreme flooding in the Jhelum basin of Kashmir, India

Abstract: The 2014 extreme flooding in Kashmir, with the peak discharge exceeding 115,000 cfs and the Jhelum River overflowing its banks, was triggered by the complex interplay of atmospheric disturbances causing widespread extreme rainfall for 7 days preceding the event. We used multisource data in GIS environment; satellites, hydro-meteorological, socioeconomic and field data, to assess the role of various factors in the flooding. The event was aggravated by the geomorphic setup of the Valley. Tributaries in the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Kashmir, a mountain region nestled in the north-western extreme of the Himalaya, has experienced a significant influence of global climate change over the last few decades (Immerzeel et al, 2010;Romshoo et al, 2015;Murtaza and Romshoo, 2017;Romshoo et al, 2017). Based on long-term records of temperature and precipitation, Zaz et al (2019) recently reported a rise of 0.8 • C in average annual temperature over the last half a century in Kashmir Himalaya.…”
Section: Introductionmentioning
confidence: 99%
“…Kashmir, a mountain region nestled in the north-western extreme of the Himalaya, has experienced a significant influence of global climate change over the last few decades (Immerzeel et al, 2010;Romshoo et al, 2015;Murtaza and Romshoo, 2017;Romshoo et al, 2017). Based on long-term records of temperature and precipitation, Zaz et al (2019) recently reported a rise of 0.8 • C in average annual temperature over the last half a century in Kashmir Himalaya.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme weather events like anomalously large floods and unusual drought conditions associated with changes in climate play havoc with livelihoods of citizens even of developed societies, particularly in coastal and mountainous areas. Jammu and Kashmir, India, located in the western Himalayan region, is one such cataclysmically formed mountainous region where the significant influence of climate change on local weather has been observed for the last few decades: (1) shrinking and reducing glaciers, (2) devastating floods, (3) decreasing winter duration and rainfall, and (4) increasing summer duration and temperature (Solomon et al, 2007;Kohler and Maselli, 2009;Immerzeel et al, 2010;Romshoo et al, 2015Romshoo et al, , 2017. Western disturbances (WDs) are considered one of the main sources of winter precipitation for the Jammu and Kashmir region, which brings water vapor mainly from the tropical Atlantic Ocean, Mediterranean Sea, Caspian Sea and Black Sea.…”
Section: Introductionmentioning
confidence: 99%
“…The harmful social, financial, and ecological impacts of declining biodiversity and degrading water quality are a matter of concern (Verma et al, 2001;Bassi et al, 2014). Most of these wetlands used to act as buffers soaking flood waters but the encroachment and infrastructure development within these wetlands has reduced their water holding capacity, increasing the vulnerability of people toward flooding (Romshoo et al, 2017). The central business hub of Srinagar, the capital city, is often affected during a normal precipitation event as the drainage channels that used to drain out storm water runoff have mostly been taken over by concrete surfaces (Rashid and Naseem, 2008).…”
Section: Current Status Of Wetlands In Srinagar Citymentioning
confidence: 99%